2018
DOI: 10.1016/j.quaint.2017.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Limnological changes in South Carpathian glacier-formed lakes (Retezat Mountains, Romania) during the Late Glacial and the Holocene: A synthesis

Abstract: Remains of aquatic biota preserved in mountain lake sediments provide an excellent tool to study lake ecosystem responses to past climate change. In the PROLONG project a multiproxy study was performed on sediments of glacier-formed lakes from the Retezat Mountains, Southern Carpathians (Romania). The studied lakes (Lake Brazi and Gales) are situated on the northern slope of the mountain at different altitudes (1740 m and 1990 m a.s.l.). Our main objectives were 1) to describe the main limnological changes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 61 publications
4
7
0
Order By: Relevance
“…Changes detected in stable isotope records are of similar scale, and changes are also observed in many other proxy climate records, e.g. in pollen, chironomid, diatom and geochemical stratigraphies (Buczkó et al 2012;Braun et al 2013;Tóth et al 2018).…”
Section: Discussionsupporting
confidence: 65%
“…Changes detected in stable isotope records are of similar scale, and changes are also observed in many other proxy climate records, e.g. in pollen, chironomid, diatom and geochemical stratigraphies (Buczkó et al 2012;Braun et al 2013;Tóth et al 2018).…”
Section: Discussionsupporting
confidence: 65%
“…This is in agreement with other studies of European peatlands (Ratcliffe et al, 2018), where rapid CARs are reconstructed in the early Holocene as a result of warm temperatures, a reflection of the key role temperature plays in CARs (Charman et al, 2009). Regionally, our data reflect the impact of warmer than present conditions and lower than present precipitation levels and higher seasonality reconstructed from multi-proxy records (Buczkó et al, 2013;Davis et al, 2003;Feurdean et al, 2008;Magyari et al, 2009;Tóth et al, 2018Tóth et al, , 2015 and modelled data which coincided with higher than present (summer) insolation (Berger and Loutre, 1991). During the mid-Holocene (7000 -3000 yr BP), CARs were generally low, with our composite record reconstructing a decreasing trend until 4000 yr BP (Fig.…”
Section: Changing Rates Of Carbon Accumulation During the Holocenesupporting
confidence: 93%
“…This is in agreement with other studies of European peatlands (Ratcliffe et al, 2018), where rapid CARs are reconstructed in the early Holocene as a result of warm temperatures; this is a reflection of the key role that temperature plays in CARs (Charman et al, 2009). Regionally, our data reflect the impact of warmer-than-present conditions and lower-than-present precipitation levels as well as higher seasonality reconstructed from multi-proxy records (Buczkó et al, 2013;Davis et al, 2003;Feurdean et al, 2008;Magyari et al, 2009;Tóth et al, 2015Tóth et al, , 2018 and modelled data which coincided with higher-than-present (summer) insolation (Berger and Loutre, 1991).…”
Section: Changing Rates Of Carbon Accumulation During the Holocenesupporting
confidence: 92%
“…As such, understanding the history of carbon accumulation in peatlands is important for critically assessing the terrestrial carbon cycle in our anthropogenically altered world (Hugelius et al, 2020;Loisel et al, 2021). Model-derived estimates of future climatic change suggest that peatlands will act as an efficient carbon sink as climate warms (Gallego-Sala et al, 2018), as observed in reconstructions of warm periods in Earth's past (Treat et al, 2019). However, this conclusion is far from certain, as land-use-driven degradation of peat since the 1960s has led to peatlands acting as a net source of carbon (Leifeld et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation